Penetapan Kadar Nikotin Tembakau Gayo (Nicotiana tabacum L) Menggunakan Metode Titrasi Asidimetri dan GC-MS. - Rezky , Deswita Ina; Supiyani, Supiyani; Daulay, Anny Sartika; Lubis , Minda Sari (Journal of Pharmaceutical and Sciences, 2025)
Background: Gayo tobacco (Nicotiana tabacum L.) is known for its distinctive quality and is highly sought after, particularly among young adults. This tobacco contains nicotine, a compound that plays a significant role in influencing human behavior, acting both as a stimulant and as a raw material for cigarette production. Understanding the nicotine content in Gayo tobacco is crucial for assessing its potential industrial applications and its impact on health. Objective: This study aimed to determine the nicotine content in Gayo tobacco leaves and analyze it using acidimetric titration and GC-MS methods to obtain more accurate results. Methods: This research employed two analytical methods: acidimetric titration for quantitative nicotine determination and Gas Chromatography-Mass Spectrometry (GC-MS) for qualitative analysis of other chemical compounds in the Gayo tobacco leaf extract. The tobacco leaf samples were obtained from the Gayo region of Aceh and extracted using 96% ethanol. Results: The study revealed that the nicotine content in Gayo tobacco leaves was 1,3% based on acidimetric titration, while the ethanol extract showed a higher nicotine concentration of 2.5%. GC-MS analysis identified various other compounds, including piperidine derivatives, terpenoids, and aromatic compounds, which have potential pharmaceutical and industrial applications. Conclusion: This study successfully determined the nicotine content in Gayo tobacco leaves using acidimetric titration and GC-MS. The findings provide a comprehensive overview of the chemical composition of Gayo tobacco, serving as a foundation for further research into its applications in pharmaceuticals and other industries.